2018
DOI: 10.1186/s13059-018-1518-x
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing accurate non-homologous end joining for efficient precise deletion in CRISPR/Cas9-mediated genome editing

Abstract: BackgroundMany applications of CRISPR/Cas9-mediated genome editing require Cas9-induced non-homologous end joining (NHEJ), which was thought to be error prone. However, with directly ligatable ends, Cas9-induced DNA double strand breaks may be repaired preferentially by accurate NHEJ.ResultsIn the repair of two adjacent double strand breaks induced by paired Cas9-gRNAs at 71 genome sites, accurate NHEJ accounts for about 50% of NHEJ events. This paired Cas9-gRNA approach underestimates the level of accurate NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 60 publications
8
91
0
Order By: Relevance
“…Herein, we have shown that the use of two guide RNAs to drive Cas9 cutting in adult cells facilitates the precise deletion of the sequences between them and reduces, or even eliminates, the heterogeneity of the error-prone NHEJ, allowing the knock down or knock out of the desired gene and the generation of cellular or animal models, with an almost homogeneous genotype. Previous works have indicated the preference for the NHEJ repair by the precise deletion between the two DSB generated when two guides are used simultaneously(Guo et al 2018). Here, we demonstrate that this characteristic facilitates the generation of cellular and animal models with a more homogeneous and controlled genotype modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we have shown that the use of two guide RNAs to drive Cas9 cutting in adult cells facilitates the precise deletion of the sequences between them and reduces, or even eliminates, the heterogeneity of the error-prone NHEJ, allowing the knock down or knock out of the desired gene and the generation of cellular or animal models, with an almost homogeneous genotype. Previous works have indicated the preference for the NHEJ repair by the precise deletion between the two DSB generated when two guides are used simultaneously(Guo et al 2018). Here, we demonstrate that this characteristic facilitates the generation of cellular and animal models with a more homogeneous and controlled genotype modification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been proposed as a potential therapeutic option by eliminating mutated exons and recovering an almost normal although functional protein(Ousterout et al 2015; Bonafont et al 2019). Guo et al studied the efficacy of the NHEJ-precise deletion (NHEJ-PD) and how this process acts when guides are separated 23-148 apart, being the precise deletion of the DNA material between the two guide cuts the most common event(Guo et al 2018). Thus, the use of two guides that could delete a defined DNA fragment and alter the open reading frame of the affected locus in an efficient and pseudo-controlled way could be used to generate KO models for the study of the biology of the cell or for the generation of cellular or animal models of rare diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A kinetic analysis of Cas9 break repair suggested that cells primarily invoke error-prone pathways to slowly repair Cas9 breaks in a single round (Brinkman et al, 2018). Conversely, experiments inducing adjacent Cas9 breaks or modulating DNA repair with non-homologous single-stranded DNA implied that cells invoke error-free repair pathways that enable repeated rounds of Cas9 binding and eviction preceding eventual end-point mutation (Guo et al, 2018; Richardson et al, 2016a). We found that knockdown of FACT reduces Cas9-induced HDR and increases indels.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches rely on homology-directed repair (HDR) to introduce a new sequence at the double-stranded break. Larger editing events can be produced by simultaneously delivering two nucleases targeted to different sequences on the same locus, which can lead to large deletions via excision of the intervening genomic sequence [3][4][5][6][7] . Generating excisions with paired CRISPR gRNAs is an attractive means to engineer complete loss of gene function, map regulatory regions, study 3D genome organization and model deletioninduced diseases.…”
Section: Introductionmentioning
confidence: 99%